2022
DOI: 10.1063/5.0076712
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Urbach tail in cesium lead halide perovskites

Abstract: The role of structural and dynamical disorder in semiconductors is a topic of fundamental relevance because of its contribution to the spectral line shape of the photoluminescence, and it plays a major role in ruling the carrier transport properties at the band edge. In this regard, a class of semiconductors, i.e., halide perovskites, deeply investigated in the last decade, shows a peculiar degree of disorder, which has only been recently under investigation. The interest to study disorder in halide perovskite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…This value is in agreement with literature data [ 25 ] and with the RT PL spectrum measured for the 1.5 µm thick sample shown in Figure 5 b, which peaked at (2.998 ± 0.002) eV. In the inset of Figure 5 b, the PL spectrum is shown in log scale, evidencing the presence of the high-energy tail coming from the recombination of the thermalized distribution of excitons and carriers, while the low-energy tail arises from the absorption Urbach tail [ 26 ]. In Figure 6 a, increasing the temperature, we observe a reduction of the intensity of roughly a factor 40 and a red shift of the PL peak energy of 7 meV.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This value is in agreement with literature data [ 25 ] and with the RT PL spectrum measured for the 1.5 µm thick sample shown in Figure 5 b, which peaked at (2.998 ± 0.002) eV. In the inset of Figure 5 b, the PL spectrum is shown in log scale, evidencing the presence of the high-energy tail coming from the recombination of the thermalized distribution of excitons and carriers, while the low-energy tail arises from the absorption Urbach tail [ 26 ]. In Figure 6 a, increasing the temperature, we observe a reduction of the intensity of roughly a factor 40 and a red shift of the PL peak energy of 7 meV.…”
Section: Discussionmentioning
confidence: 77%
“…The dependence of E U on the temperature is shown in Figure 11 b where the red arrows indicate the temperatures where the phase transitions are reported in the literature [ 13 , 16 , 21 , 30 ]. A flattening in the Urbach energy is found in a restricted temperature interval around each phase transition: such behavior represents a significant deviation from what was found and expected, considering the origin of the Urbach tail in halide perovskites related to the dynamic disorder induced by the lattice vibration [ 26 ]. The way the experiment was performed (changing T in steps and waiting several minutes after each step in order to stabilize T) excludes that the pedestals are related to latent heat-related effects; therefore, additional contributions as strain release between the film and the substrate and within the grains in the film have to be invoked to explain the behavior of E U at the phase transition temperatures.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The temperature-dependent PL spectra in a log scale of GC-Ca were measured to analyze the Tail1. As shown in Figure 1 b, the low energy tail in the PL spectra (in a log scale) of GC-Ca is nearly mono-exponential in the range of 20–300 K, which suggests that the Tail1 of CsPbBr 3 QDs in the glass matrix is weak related to the Urbach Tail [ 40 ]. Compared with tails on both sides of the spectrum ( Figure 1 a), the main peak plays a dominant role in the change of spectral shape and PL peak position.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike monodispersed QDs, the spontaneous thermal expansion of QDs in a glass matrix is affected (suppressed/reinforced) by the mismatch between the matrix and QDs. Therefore, we suggested that the difference of thermal expansion mismatch value leads to the distinct optical properties of CsPbBr 3 QDs in different matrixes [ 40 ]. Additionally, the abnormal PL linewidth evolution at low temperatures (120–160 K) can also be attributed to the change of phase transition temperature caused by thermal expansion mismatch.…”
Section: Discussionmentioning
confidence: 99%